2008
DOI: 10.1089/acm.2006.6397
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Blood Total Glutathione Status and Lymphocyte Function Followingα-Lipoic Acid Supplementation in Patients with HIV Infection

Abstract: Supplementation with alpha-lipoic acid may positively impact patients with HIV and acquired immune deficiency syndrome by restoring blood total glutathione level and improving functional reactivity of lymphocytes to T-cell mitogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“…4 Furthermore, reduced glutathione concentration and/or a disproportionate ratio of GSH:GSSG has been associated with a number of diseases, including cancer, human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS), hepatitis, type 2 diabetes, Parkinson's disease, and cystic fibrosis. 2,[8][9][10][11][12][13][14] Although no experimental research to date has demonstrated disease prevention from GSH supplementation or other strategies to specifically increase GSH, observational research suggests increased dietary glutathione intake has been associated with reduced risk for oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…4 Furthermore, reduced glutathione concentration and/or a disproportionate ratio of GSH:GSSG has been associated with a number of diseases, including cancer, human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS), hepatitis, type 2 diabetes, Parkinson's disease, and cystic fibrosis. 2,[8][9][10][11][12][13][14] Although no experimental research to date has demonstrated disease prevention from GSH supplementation or other strategies to specifically increase GSH, observational research suggests increased dietary glutathione intake has been associated with reduced risk for oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of the ALA is hampered by its instability and its rapid metabolism, suggesting that formulations containing ALA, in a form ensuring its stability and improving its bioavailability, can have important applications as medicines, nutritional supplements or cosmeceuticals [76] . Also, ALA as a mitochondrial cofactor termed 'mitochondrial nutrient' has been tested in a number of clinical trials such as alcohol-related liver disease [77] , diabetes-associated neuropathy [78] , heart disease [79] , HIV-1-related lipoatrophy [80] and mitochondrial diseases disease [81] . Also, there are only two clinical trial papers.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies support its use in the ancillary treatment of many diseases, such as diabetes, cardiovascular, neurodegenerative, autoimmune diseases, cancer and AIDS (Khalili et al 2014;Shinto et al 2014;Sancheti et al 2013a;Gębka et al 2014;Padmalayam 2012;Yamasaki et al 2014;Jariwalla et al 2008;Gorąca et al 2011) . In addition to its anti-oxidative role, LA supplementation in diet modulates the inflammatory response by inhibiting IL-6 and TNF-α expression (Li et al 2014) . LA significantly inhibited LPS-induced production of nitric oxide and TNF-α via an attenuated activation of NF-κB and activator protein-1 (Kiemer et al 2002) .…”
Section: Discussionmentioning
confidence: 99%